2017
DOI: 10.1136/bmjgh-2017-000408
|View full text |Cite
|
Sign up to set email alerts
|

Improving postpartum care delivery and uptake by implementing context-specific interventions in four countries in Africa: a realist evaluation of the Missed Opportunities in Maternal and Infant Health (MOMI) project

Abstract: Postpartum care (PPC) has remained relatively neglected in many interventions designed to improve maternal and neonatal health in sub-Saharan Africa. The Missed Opportunities in Maternal and Infant Health project developed and implemented a context-specific package of health system strengthening and demand generation in four African countries, aiming to improve access and quality of PPC. A realist evaluation was conducted to enable nuanced understanding of the influence of different contextual factors on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Therefore, they were motivated to help their community in matters of health. We found, as in the other MOMI project countries (Kenya, Malawi, Mozambique), that the trust between CHWs and their community motivated them to provide an effective bridging function [20].…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, they were motivated to help their community in matters of health. We found, as in the other MOMI project countries (Kenya, Malawi, Mozambique), that the trust between CHWs and their community motivated them to provide an effective bridging function [20].…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the issues of facility under-staffing [25], over-burdening of the providers by existing workloads [25] and demotivation by the lack of organizational-level accountability, support and incentive structures [26] need to be addressed. These factors likely contribute to shortened length of stay at the facility after delivery, which in turn, could lead to less mothers and newborns being checked before discharge due to time and space constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization through social networks with an appropriate timetable as implemented by the female CHW proved positive for behavioral change and raised attention to PPC [28,29] . Monitoring and supervision were revealed to be an important factor of success for the interventions [12] . Women in rural areas had a higher rate of home visits than women in urban areas.…”
Section: Activities and In Uencing Factorsmentioning
confidence: 99%
“…However, most of these evaluations have focused on the effectiveness, feasibility [8,9] or impact of these programs [10] Few impact evaluation studies have examined the context and mechanisms that led to the observed results [11,12] . In addition, the majority of these evaluations used counterfactual elements or control versus intervention groups to attribute an observed result to a given program [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation